2021
DOI: 10.2131/jts.46.311
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of primary oxidative metabolites of thalidomide in rats and in chimeric mice humanized with different human hepatocytes

Abstract: The approved drug thalidomide is teratogenic in humans, nonhuman primates, and rabbits but not in rodents. The extensive biotransformation of 5′-hydroxythalidomide after oral administration of thalidomide (250 mg/kg) in rats was investigated in detail using liquid chromatography-tandem mass spectrometry. Probable metabolites 5′-hydroxythalidomide sulfate and glucuronide were extensively formed, with approximately tenfold and onefold peak areas, respectively, to the primary 5′-hydroxythalidomide measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Such intermediates can be trapped by glutathione (GSH) to give GSH adducts (Yamazaki et al, 2016a) that have been confirmed in vivo in humanized-liver mouse models after oral doses of 100 mg/kg thalidomide . Although five control mice had no apparent adverse effects after an oral dose of 270 mg/kg (~1 mmol) thalidomide/kg, an oral LD 50 of 270 mg/kg was observed for humanized-liver mice (two of five animals died after 2 days) (Miura et al, 2021b). Differences in species susceptibility to thalidomide teratogenicity may result from differences in the primary biotransformation of the compound by drug-metabolizing enzymes.…”
Section: Brief Historical Perspectivementioning
confidence: 89%
See 1 more Smart Citation
“…Such intermediates can be trapped by glutathione (GSH) to give GSH adducts (Yamazaki et al, 2016a) that have been confirmed in vivo in humanized-liver mouse models after oral doses of 100 mg/kg thalidomide . Although five control mice had no apparent adverse effects after an oral dose of 270 mg/kg (~1 mmol) thalidomide/kg, an oral LD 50 of 270 mg/kg was observed for humanized-liver mice (two of five animals died after 2 days) (Miura et al, 2021b). Differences in species susceptibility to thalidomide teratogenicity may result from differences in the primary biotransformation of the compound by drug-metabolizing enzymes.…”
Section: Brief Historical Perspectivementioning
confidence: 89%
“…P450s have been the focus of attention in many pharmaceutical companies and industrial applications. Research on P450s using non-human primates and animal models with introduced human P450 (CYP) genes or with transplanted human hepatocytes has attracted biochemists, (Miura et al, 2021a) and of thalidomide to 5′-hydroxythalidomide and 5-hydroxythalidomide (B) (Kuwagata et al, 2021;Miura et al, 2021b). (Yamazaki et al, 1996;Yamazaki et al, 2001), whereas for FMOs, only in the third step is the flavin hydroperoxide intermediate capable of oxygenating substrates (Ziegler, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Simplified PBPK models comprising gut, liver, kidney, and central compartments were established for aniline and 2,6-dimethylaniline (Miura et al, 2021b, 2020b, 2021c, Kamiya et al, 2022a. The values used in this study for the hepatic/renal volumes and the hepatic/renal blood flow rates ( Q h / Q r ), respectively, were 0.85 mL, 0.34 mL, and 0.160 L/hr in mice and 8.5 mL, 3.7 mL, and 0.853 L/hr in rats ( Miura et al, 2021b( Miura et al, , 2021a.…”
Section: Pbpk Modeling Of Aniline and 26-dimethylanilinementioning
confidence: 99%
“…8,9 An oral dose of 270 mg (∼1 mmol)/kg of thalidomide was teratogenic for rabbits but approximately half-lethal for humanized-liver mice. 8,9 The activation of thalidomide to 5hydroxythalidomide in human placenta/livers in vitro was suggested, with autoinduction of P450 3A enzyme activity. 10,11 Determining whether autoinduction of human P450 3A enzyme activity occurs in vivo can be important in evaluating toxic potential and clinical outcome.…”
mentioning
confidence: 99%
“…Thalidomide and its metabolites were obtained from previously reported sources. , An updated TK-NOG mouse line (NOG-TKm30) was used with the approval of the Animal Ethics Committee of the Central Institute for Experimental Medicine and Life Science (Permit Number: 20060A). Humanized-liver F1 hybrid TKm30 mice (eight females weighing approximately 24–27 g; with transplanted cryopreserved human hepatocytes derived from a 5-year-old Caucasian male, Lonza, Walkersville, MD) were orally administered 100 mg/kg thalidomide daily for 4 days.…”
mentioning
confidence: 99%